Effects of in-season circuit training on physical abilities in male handball players - Hermassi, S.; Wollny, R.; Schwesig, R.; Shephard, R. J.; Chelly, M. S. (The Journal of Strength and Conditioning Research, 2019)
This study analyzed the effects of a resistance-type circuit training (RCT) program (30-35 minutes, performed twice a week for 10 weeks) on male handball players. Twenty-two male players were divided into experimental (E; age 20.3 ± 0.5 years) and control groups (C; age 20.1 ± 0.5 years). Measures before and after RCT included squat jump (SJ), countermovement jump (CMJ), 1 repetition maximum (1RM) of bench press, pull-over and back half-squats, throwing velocity (a 3-step running throw [RT], and a jump throw [JT]), repeated-sprint ability (six 2 × 15-m shuttle sprints with recording of best time for a single trial), anthropometric estimates of leg- and thigh-muscle volumes and mean thigh cross-sectional area (CSA), and a test of agility. The agility T-half test showed a significant interaction effect (p = 0.001; n2 = 0.422), with an intergroup difference in effect size (d) of 1.27 (d TG = 1.24 vs. d CG = -0.03). The SJ displayed no interaction effect. The interaction effects for half back squat (d = 2.73, n2 = 0.740) and CMJ (d = 3.76, n2 = 0.700) were large, but that for RT was smaller (n2 = 0.460) than that for JT (n2 = 0.745). The throwing velocity of C decreased for both measures, with negative effect sizes (d = -0.18 and d = -0.93, respectively). Upper-body, leg, and thigh-muscle volumes and thigh CSA increased significantly after resistance training. However, repeated-sprint parameters showed no significant changes. During the competitive season, 10 weeks of RCT with only 2 training sessions per week improved numerous measures of athletic performance in handball players, and such conditioning can be highly recommended as part of the annual training program for elite handball players.